Innovative strategies for providing menstruation-supportive water, sanitation and hygiene (WASH) facilities: Learning from refugee camps in Cox’s bazar, Bangladesh - Schmitt, Margaret L.; Wood, Olivia R.; Clatworthy, David; Rashid, Sabina Faiz; Sommer, Marni (BMC, 2022)
This article was published in the Conflict and Health by BMC [© The Author(s). 2021 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use,] and the definite version is available at: https://doi.org/10.1186/s13031-021-00346-9 The Journal's website is at: https://conflictandhealth.biomedcentral.com/articles/10.1186/s13031-021-00346-9